Proposta de diretrizes para melhoria no processo de montagem de janela de ônibus urbano - Zavistanovicz, Lucas (2013)
This work mainly aims at the analysis of the assembly process of the windows urban bus and from there, then the presentation of a proposal of guidelines for improving the assembly process of urban bus window. The current process of mounting the windows of city bus is characterized by being manual, and employees need to perform excessive effort to perform this task, and as a result, there is high employee turnover in the industry, absenteeism, time high production and risk of damage to the components of the window. In the contemplation of the present work , a study was conducted of key technical standards and resolutions dealing with the manufacture and assembly of components of urban bus window, methodologies projetuais more widespread today, the concepts of DFMA (Design for Manufacturing and Assembly) and especially the monitoring of the assembly process of urban bus windows. So then , from the projective appropriate choice of methodology , followed by applying this detailed being pointed out that the same manufacturing a device which allows the flap to be folded gasket with ease , allowing easy fitting window in the structure of urban bus.It was also demonstrated the usefulness of the concepts of DFMA (Design for Manufacturing and Assembly), and that it allows an optimization of the entire production process, such as reducing the number of parts, use of parts with different functions simultaneously among other advantages. The proposed device was modeled with the aid of Solid Works 2010, and demonstrated, through drawings and analysis of carriers of the main function , that it is a simple and useful solution that performs the function for which it was designed